Bioprotopia designing the built environment with living organisms - Bridgens, Ben; Mackenzie, Louise; Morrow, Ruth 1964- (Birkhäuser, 2023)
Designing with living materials: thoughts on the paradigm shift and an overview of the state of research What is "Bioprotopia"? It is the vision of a world with buildings that grow, self-heal and create virtuous cycles where waste from one process feeds another. A vision where the spaces that we inhabit are attuned to both the human occupants and non-human microbial ecologies. This is the first book to ground the concept of biotechnology in the built environment in tangible, large-scale prototypes. With rich visuals, it presents materials and processes that exploit the many possibilities of shaping the built environment with micro-organisms. At the same time, scientific and technical challenges are discussed, pointing to the need for a shift in thinking and culture to ensure progress. First comprehensive publication on the state of research Demonstrates the use of renewable materials in design Illustrative, scientific documentation for design professions and researchers
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mai 2023)
Keywords: Baumaterialien; Ben Bridgens; Biodesign; Biotechnologie; HBBE.; Klimawandel; Louise Mackenzie; Materialinnovation; New Castle University; Pilze; Pilzkulturen; Prototypen; Recycling; Ruth Morrow; Techno Utopie; The OME.; ARCHITECTURE / Professional Practice; Design; Baustoff; Gestaltung; Biologie; Innovation; Umwelt; Organismus; Architektur